Future agroclimatic conditions and implications for European grasslands - M. TRNKA; J. BALEK; M.A. SEMENOV; D. SEMERÁDOVÁ; M. BĚLÍNOVÁ; P. HLAVINKA; J.E. OLESEN; J. EITZINGER; A. SCHAUMBERGER; P. ZAHRADNÍČEK; D. KOPECKÝ; Z. ŽALUD (Biologia Plantarum, 2021)
Grasslands play a significant role in livestock fodder production and thus, contribute to food security worldwide while providing numerous additional ecosystem services. However, how agroclimatic conditions and adverse weather events relevant for grasslands will change across the European grassland areas has not been examined to date. Using a single reference setup for soil and management over 476 European sites defined by climate stations, we show the probability of eight selected adverse weather events with the potential to significantly affect grassland productivity under climate change and how these events vary regionally across Europe. Changes in these eight key agroclimatic indicators create markedly specific spatial patterns. We found that by 2050, the exposure of the south and west European grasslands to heat and drought may double in comparison with today and that the area with frequent occurrences of heat and drought will expand northwards. However, across Ukraine, Belarus, and the Baltic countries to southern Finland and Sweden, the likelihood of these events is likely to decrease. While changing cultivars and management strategies are unavoidable, shifting grassland production to other regions to reduce the risk may not be possible as the risk of adverse events beyond the key grassland-growing areas increases even further. Moreover, we found marked changes in the overall thermal and water regimes across European regions. The effect of adverse weather events in the future could be different in other regions of the world compared to regions in Europe, emphasizing the importance of conducting similar analyses for other major grassland producing regions. To mitigate the impact of climate change, new ways of maintaining grassland productivity need to be developed. These methods include more efficient selection of species mixtures for specific regions, including increased use of legumes and forbs; incorporation of new genetic resources, including the development of hybrid cultivars, such as Festulolium hybrids; and incorporation of state-of-the-art technologies in breeding programs and new grazing management.